2013
DOI: 10.1108/14714171311296048
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of web‐based construction project management system in China projects by Hong Kong developers

Abstract: PurposeThis paper aims to identify the challenges of Hong Kong and overseas developers in project management when undertaking real estate projects in China, and then focuses on how to mitigate and solve the problems. The proposed solution is about a concept of using the IT tool “web‐based construction project management system” (WPMS) to help assuring projects success in China. The study reported in this paper focuses on how to implement WPMS to manage construction projects in China considering the overall sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…There have been extensive studies focussing on the adoption of ICT technologies in the architectural, engineering and construction (AEC) industry. These include the adoption of enterprise resource planning systems (Chung et al, 2008(Chung et al, , 2009Yang et al, 2007;Skibniewski and Ghosh, 2009); application of geographic information system and global positioning system technologies (Bansal and Pal, 2009;Irizarry et al, 2013;Li et al, 2005;Kim and Teizer, 2014); and web-based project management solutions (Arnold and Javernick-Will, 2013;Nitithamyong and Skibniewski, 2011;Wong and Zhang, 2013). These studies focus largely on the success factors, barriers, key performance indicators and implementation strategies of adopting ICT technologies in the AEC industry with a consideration of specific context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There have been extensive studies focussing on the adoption of ICT technologies in the architectural, engineering and construction (AEC) industry. These include the adoption of enterprise resource planning systems (Chung et al, 2008(Chung et al, , 2009Yang et al, 2007;Skibniewski and Ghosh, 2009); application of geographic information system and global positioning system technologies (Bansal and Pal, 2009;Irizarry et al, 2013;Li et al, 2005;Kim and Teizer, 2014); and web-based project management solutions (Arnold and Javernick-Will, 2013;Nitithamyong and Skibniewski, 2011;Wong and Zhang, 2013). These studies focus largely on the success factors, barriers, key performance indicators and implementation strategies of adopting ICT technologies in the AEC industry with a consideration of specific context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hunsucker and Loos (1989) defined change agents as internal champions of the change who lead the transition. Wong and Zhang (2013) studied the implementation of a web-based project management system in China and found that one of the key success factors is the presence of an internal champion. Sullivan et al (2011) emphasized that change agents should have operational-level knowledge of the problems and desired solutions because this knowledge enables the individuals to effectively lead the change.…”
Section: Methodsmentioning
confidence: 99%
“…For example, BIM, which involves using software models to simulate the design and delivery process of construction works [27], has proved effective for cost and time savings in construction projects. Furthermore, this tool has fostered positive collaboration on projects [28] and made it possible to deliver more sustainable designs within the industry [29]. In addition, IoT, which involves connecting objects using the internet with a pre-set protocol involving information sensors [30], has proven to improve communication among project participants [3,4].…”
Section: Digital Technologies In Constructionmentioning
confidence: 99%